Representação da informação de cibercordéis em blogs: uma análise sob a luz da semântica discursiva - Gaudêncio, Sale Mário (2014)
This investigation which had as general objective analyze the representation of information of cibercordéis in blogs through semantic procedures of theming and figurativization, central elements to the process of indexing in the methodology recognized as discursive semantic. Is justified by understanding that it is increasingly important bring to the focus of scientific research the process of information representation, especially for realize that there are multiple memory locations that require scientific analysis. Is used as corpus the cibercordel that makes use of the integrative flexibility of internet, especially the blogs dynamic with the intention of understand, represent, preserve and promote their cultural productions. The cibercordéis enable the appropriate environment to be treated from the perspective of informational representation, timely for presenting textual elements such as themes, pictures, inspirations, aspirations, topics, in other words, their specificities constructed through popular poetry, which in this case, appropriates the web to be perpetuated within the cyberspace. From the research, it was found that the representation of the information through discursive semantic is shown as another real way to index documents, especially for observing all its textual features, concrete and abstract aspects, focusing on the indexing, through Greimasian semantic, as a methodological conception, significantly reduces the subjectivity inherent to the information professional, plus approach substantially from the documentary language, for producing a constant interdisciplinary exchange, relating figures to natural language and themes to artificial language. For this reason, the documents understood as cibercordéis are amenable to representation and preservation of informational, thus, allowing safeguard the collective memory and strengthen a recovery of organized information in a fast and systematic way.